Design Organizational Health and Organizational Performance through the Workplace Spirituality, Adaptive Innovation Capabilities and Involvement HRM Practices: An Indonesia Cased Study - H. S., Ikhwan; Himawati, Ditiya; Utomo, Joko; Yanti, Etyca Rizky (International Review of Management and Marketing, 2024)
The purpose of this study is to examine the effect of Workplace Spirituality (WPS), Adaptive Innovation Capabilities (AIC) and Involvement HRM Practices (HRM-P) on organizational performance (OP) mediated by organizational health (OH). This study uses primary data collected through a survey using a questionnaire distributed to managers in 150 finance companies operating in Indonesia using a convenience sampling method for 6 months. The questionnaire underwent validation and reliability assessment through factor analysis and internal consistency analysis using Cronbach's Alpha. Data examination involved assessing the relationship between research variables via bivariate correlation. Additionally, the relationship model, encompassing both direct and mediation models, underwent testing using Structural Equation Modeling (SEM) with the SmartPLS 3.0 software. The results of testing the five variables show that the correlation between the variables studied is significant and quite strong. This shows that Workplace Spirituality, Adaptive Innovation Capability, Involvement HRM Practices, and Organization Health are related to Organization Performance. Furthermore, the organizational health variable is proven to mediate the relationship between the three variables on organizational performance. The conclusion of this study are limited to the finance company sector, perhaps further research needs to be developed on non-financial companies which opens up the possibility of further research and its practical and theoretical implications can be studied further. Research gaps as a basis for future research directions are still scarce and needed.